Self-esteem moderates the associations between body-related self-conscious emotions and depressive symptoms. (May 2019) - Brunet, Jennifer; Pila, Eva; Solomon-Krakus, Shauna; Sabiston, Catherine M; O'Loughlin, Jennifer
The objectives of this study were to describe the cross-sectional associations between body-related self-conscious emotions and depressive symptoms in young adults and examine self-esteem as a moderator of these associations. Data from a population-based sample of 811 young adults were analyzed using hierarchical multivariate linear regression analysis. Body-related shame ( β = .26) and guilt ( β = .25) were positively related to frequency of depressive symptoms. Self-esteem was negatively related to frequency of depressive symptoms ( β = −.46). Self-esteem moderated the association between body-related guilt and frequency of depressive symptoms. These findings suggest promoting self-esteem may help to reduce the negative effects of body-related guilt on depressive symptoms.